Evaluasi Sistem Informasi Media Online Menggunakan Metode Technology Acceptance Model (TAM) - arief Ichwani; Eva Milenia Surya Buana (Jurnal Komputasi, 2021)
Abstract — Lensapena.id is a news provider website that has been established since 2019. However, many people do not know Lensapena.id and the public's lack of intention in using the Lensapena.id. Therefore, to find out the acceptance of Lensapena.id, it is necessary to evaluate the acceptance. The evaluation method used in this study is Technology Acceptance Model (TAM) with 5 variables, namely Perceived Ease Of Use, Perceived Usefulness, Attitude To the Act, Behavioral Intention and Actual System Usage. Data collection was done by questionnaires, observations and interviews. The sample assumption used in this study is 100 general public. The results showed that the level of acceptance of the Lensapena was worthy of Neutral which had a value of 4.4 and there were 4 accepted relationships, namely Attitude Toward The Act on Behavioral Intention, Behavioral Intention on Actual System Usage, Perceived Ease Of Use on Attitude Toward The Act, Perceived Ease Of Use on Perceived Usefulness and 2 rejected relationships, namely Perceived Usefulness on Attitude Toward The Act and Perceived Usefulness on Behavioral Intention. Based on the research conducted, several recommendations are given to increase acceptance on the Lensapena.id.